Analysis of age‐associated alternation of SCSA sperm DNA fragmentation index and semen characteristics of 1790 subfertile males in China. Issue 12 (14th September 2020) - Lu, Ruijing; Chen, Xian; Yu, Weijian; Jiang, Fan; Zhou, Xiyou; Xu, Yang; Wang, Feng
Abstract: Background: It has been identified that incidence of infertility was about 20% among couples worldwide, about 50% caused by male elements. However, conventional semen laboratory detections could not handle clinical needs, which led to more comprehensive parameters for male fertility evaluation. We aimed to investigate the clinical relationship of age‐linked changes and the sperm chromatin structure assay (SCSA) sperm DNA fragmentation index (DFI), and routine semen characteristics among subfertile Chinese males. Methods: 1790 clinical semen specimens were enrolled from February 2018 to October 2019. Clinical and laboratory data including routine semen analyses, sperm DFI, and sperm morphology were collected and showed age‐related alterations in semen parameters. Results: Our results, displayed an increase in sperm DFI with age, were demonstrated in three age‐groups, particularly within the ≥35‐year cohort. There were positive and inverse correlations of sperm DFI with abnormal semen characteristics and with normal morphological parameters, respectively. Furthermore, age, sperm morphology, concentration, and progressive motility, immotile sperm percentage, semen volume, sperm survival, and high acridine orange DNA stainability (indicating immature forms) were found to be independent risk factors affecting sperm DNA integrity. Likewise, men aged ≥35 years had a higher sperm DFI than did normozoospermic men in the overall cohort. Routine semen characteristics, sperm DFI, and morphology tended to alter with age. Conclusions: The SCSA sperm DFI showed the greatest clinical application in the assessment of male fertility in this study, which should help infertility clinics decide on reproductive options for the treatment of older infertile couples. Abstract : An increase of sperm DFI with age‐linked, particularly in the males over 35 years.